Discovery of Therapeutic Targets and Potential Drugs to Fight Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2): A Review - Arif Nur Muhammad Ansori (Indian Journal of Forensic Medicine & Toxicology, 2021)
SARS-CoV-2, the causative agent of COVID-19, has led to more than two million deaths worldwide. Thereare currently no specific therapies approved to treat COVID-19 and drug repositioning, rather than newdrug discovery, which may be the best short-term option for controlling the pandemic. In this review, theauthor discusses important viral targets such as the papain-like protease, RNA-dependent RNA polymerase,3-chymotrypsin-like protease, and spike protein. The information about chemical compounds and targetsprovided in this review will aid further in vitro and in vivo studies to discover drugs to treat COVID-19.